Body size data collected non-invasively from drone images indicate a morphologically distinct Chilean blue whale (Balaenoptera musculus) taxon - Leslie, MS; Perkins-Taylor, CM; Durban, JW; Moore, MJ; Miller, CA; Chanarat, P; Bahamonde, P; Chiang, G; Apprill, A (Endangered Species Research, 2020)
The blue whale Balaenoptera musculus (Linnaeus, 1758) was the target of intense commercial whaling in the 20th century, and current populations remain drastically below pre-whaling abundances. Reducing uncertainty in subspecific taxonomy would enable targeted conservation strategies for the recovery of unique intraspecific diversity. Currently, there are 2 named blue whale subspecies in the temperate to polar Southern Hemisphere: the Antarctic blue whale B. m. intermedia and the pygmy blue whale B. m. brevicauda. These subspecies have distinct morphologies, genetics, and acoustics. In 2019, the Society for Marine Mammalogy’s Committee on Taxonomy agreed that evidence supports a third (and presently unnamed) subspecies of Southern Hemisphere blue whale subspecies, the Chilean blue whale. Whaling data indicate that the Chilean blue whale is intermediate in body length between pygmy and Antarctic blue whales. We collected body size data from blue whales in the Gulfo Corcovado, Chile, during the austral summers of 2015 and 2017 using aerial photogrammetry from a remotely controlled drone to test the hypothesis that the Chilean blue whale is morphologically distinct from other Southern Hemisphere blue whale subspecies. We found the Chilean whale to be morphologically intermediate in both overall body length and relative tail length, thereby joining other diverse data in supporting the Chilean blue whale as a unique subspecific taxon. Additional photogrammetry studies of Antarctic, pygmy, and Chilean blue whales will help examine unique morphological variation within this species of conservation concern. To our knowledge, this is the first non-invasive small drone study to test a hypothesis for systematic biology.